microRNAs as biomarkers of risk of major adverse cardiovascular events in atrial fibrillation - de los Reyes-García, Ascensión M.; Zapata-Martínez, Laura; Águila, Sonia; Lozano, María L.; Martínez, Constantino; González-Conejero, Rocío (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation is a complex and multifactorial disease. Although prophylactic anticoagulation has great benefits in avoiding comorbidities, adverse cardiovascular events still occur and thus in recent decades, many resources have been invested in the identification of useful markers in the prevention of the risk of MACE in these patients. As such, microRNAs, that are small non coding RNAs whose function is to regulate gene expression post-transcriptionally, have a relevant role in the development of MACE. miRNAs, have been investigated for many years as potential non-invasive biomarkers of several diseases. Different studies have shown their utility in the diagnosis and prognosis of cardiovascular diseases. In particular, some studies have associated the presence of certain miRNAs in plasma with the development of MACE in AF. Despite these results, there are still many efforts to be done to allow the clinical use of miRNAs. The lack of standardization concerning the methodology in purifying and detecting miRNAs, still provides contradictory results. miRNAs also have a functional impact in MACE in AF through the dysregulation of immunothrombosis. Indeed, miRNAs may be a link between MACE and inflammation, through the regulation of neutrophil extracellular traps that are a key element in the establishment and evolution of thrombotic events. The use of miRNAs as therapy against thromboinflammatory processes should also be a future approach to avoid the occurrence of MACE in atrial fibrillation.